Adaptação cultural para o Brasil da matriz de avaliação das atividades e participação para autismo (MAAPA) - Miccas, Camila (2015)
The Matrix of Assessment of Activities and Participation (MAAPA) is a tool developed with grounded on the International Classification of Functioning, Disability and Health for Children and Youth (ICF-CY), which assesses children with autismo, aged between 0 and 6 years and was developed in Portugal. The present research aimed to accomplish the cultural adaptation of the instrument described above for the Portuguese of Brazil and check its applicability to the Brazilian population through the use of MAAPA to evaluate children diagnosed with autism and signs of autism, who attend the schools of early childhood education and elementary school in the city of Barueri. The process of cultural adaptation of the instrument follow the rules indicated in the reference literature, namely, evaluation by expert judges and technical use "Focus Group". To evaluate the applicability of the instrument to the Brazilian population, the same was used by three different observers, assessing the same group of children. The main results were: specific adaptations in terms and expressions after evaluation of the instrument by the judges and experts also after the use of the technique of the "focus group", making the instrument more clear and easy to understand for the Brazilian population. As to the applicability of MAAPA, the instrument was shown to be sensitive, identifying differences in the results of the three observers and able to draw a map specific functional of each student, allowing the teacher to perform with greater knowledge planning and interventions